The Effect of Vitamin C Addition on Epigallocatechin Gallate (EGCG) Stability in Green Tea Solution - Alief Putriana Rahman; Djoko Agus Purwanto; Isnaeni Isnaeni (Universitas Airlangga, 2019)
Background: Epigallocatechin gallate (EGCG) is the most abundant green tea catechin with a powerful antioxidant effect to prevent cancer cells. EGCG in green tea solution is highly susceptible to degradation, this it is urgent to increase the stability of EGCG by vitamin C addition. Vitamin C can regenerate radical EGCG to be normal EGCG. Objective: This research aim was to determine percent of decreased level of EGCG before and after vitamin C addition. Methods: This paper was focused on enhancing the stability of EGCG by 1 mg (GTVC1), 1.5 mg (GTVC2), 2 mg (GTVC3), 2.5 mg (GTVC4) and 3 mg (GTVC5) of vitamin C addition to 10 g/L of green tea solution concentration. Evaluations of EGCG were conducted at 0 days, 1 day, 2 days, 3 days, and 4 days of storage time. EGCG was analyzed using thin layer chromatography (TLC) densitometry methods. The stability of EGCG was determined by % of decreased EGCG. Results: Percent of loss of EGCG in GT, GTVC1, GTVC2, GTVC3, GTVC4 and GTVC5 after 4 days storage were 19.93%, 10.89%, 21.08%, 18.18%, 28.56%, and 9.76%, respectively. Conclusion: This study showed that in 4 days storage, the decreased level of EGCG in green tea solution with 3 mg of vitamin C addition (GTVC5) was 9.76% which was smaller than green tea solution without vitamin C addition (GT) which EGCG decreasing 19.93%.